PENGARUH WORK-FAMILY CONFLICT DAN STRESS KERJA TERHADAP KINERJA PENYIDIK MELALUI MOTIVASI KERJA - Yuliani Yuliani; Liswandi Liswandi; Amri Darwis (JURNAL LENTERA BISNIS, 2021)
This research was conducted at Special Crime Directorate of the National Police Criminal Investigation Unit with the title Effect of Work-Family Conflict and Work Stress on Investigator Performance through Motivation as an Intervening Variable. The formulations of the problems are: (1) how do work-family conflict and work stress affect the motivation of investigators; (2) how do work-family conflict and work stress affect the performance of investigators; (3) how do work motivation affect the performance of investigators; and (4) how do work-family conflict and work stress affect the performance of investigators. This research is a quantitative research, carried out in a cross-sectional manner, using the method of causality by conducting hypothesis testing. The data used are primary data obtained by distributing questionnaires directly to 139 respondents. Data analysis uses a structural equation model or Structural Equation Model (SEM) with data processing using Partial Least Square (PLS) version 3. This analysis is used to determine how much influence the independent variables are Work Family-Conflict and Job Stress on the dependent variable are Investigator Performance and Work Motivation. The results showed that: (1) work-family conflict and work stress have a negative and significant effect on the motivation of investigators; (2) work-family conflict and work stress have a negative and significant effect on the performance of investigators; (3) work motivation has a positive and significant effect on the performance of the investigators; and (4) work-family conflict and work stress have a negative and significant effect on the performance of investigators through work motivation.Keywords: Work-Family Conflict, Job Stress, Motivation, Investigator Performance.